Preparation and implementation of pancreas transplantation programme in diabetic patients - Bartos, V; Vanĕk, I; Saudek, F; Pavel, P; Vondra, K; Kocandrle, V (Czechoslovak medicine, 1987)
Having reviewed the state-of-the art trends in pancreas transplantation over the world, the authors describe their own experimental studies preceding elaboration of the technique of pancreatic segment transplantation with duct obliteration. In their technique, the splenic artery is interposed in the course of the iliac arteries of the recipient. The procedure of the selection of diabetic patients suitable for a combined pancreas and kidney transplantation is presented. The results in 13 recipients with insulin-dependent diabetes and progressed organ complications are evaluated. In these patients a combined pancreas and kidney transplantation is of a better prognosis compared with the conventional treatment methods.
Keywords: diabetické nefropatie; diabetes mellitus 1. typu; Male; Postoperative Complications; Graft Survival; transplantace slinivky břišní; Dogs; pankreas; experimentální diabetes mellitus; Adult; Pancreas Transplantation; dospělí; Pancreas; mužské pohlaví; pooperační komplikace; arteria lienalis; Arteriovenous Shunt, Surgical; arteriovenózní zkrat; Animals; Diabetic Nephropathies; lidé; ženské pohlaví; Kidney Transplantation; transplantace ledvin; Humans; zvířata; Splenic Artery; přežívání štěpu; vena lienalis; Splenic Vein; psi; Diabetes Mellitus, Type 1; Diabetes Mellitus, Experimental; Female; lidé středního věku; Middle Aged